Hydrogen adsorption of novel N-doped carbon nanotubes functionalized with scandium - Mananghaya, Michael (Animo Repository, 2015)
The implementation and effectiveness of the ability of Nitrogen doped Carbon Nanotube with divacancy (4ND-CNxNT) that is decorated with Sc for Hydrogen adsorption was evaluated with the aide of spin-unrestricted Density Functional Theory formalism. The composite material Sc/4ND-CNxNT has an excellent quality as a media for hydrogen storage characterized by strong binding such that each Sc can hold up to five hydrogen molecules. Detailed structural and electronic properties were reported starting from one up to five hydrogen molecules absorbed. © 2015 Hydrogen Energy Publications, LLC.